Model of Positivization of Shari'ah Economic Law in Indonesia: A Study of Bank Indonesia Regulations 2008-2023 - Ahmad Munif; Nur Hasan; Siti Tatmainul Qulub (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2024)
The objective of this article is to clarify the regulations established by Bank Indonesia (PBI) from 2008 to 2023 in relation to sharia-compliant banking. PBI represents a regulatory framework incorporating or referencing the Fatwa DSN-MUI, as mandated by the Law on Banking Regulations for Islamic Banking, which requires that the Fatwa DSN-MUI serve as a reference point for the principles of Islamic banking. This study aims to address two research questions. The first question concerns the transformation of the DSN-MUI fatwa into a PBI from 2008 to 2023. The second question is an examination of the patterns of transformation. This research is a qualitative study within the field of normative legal research. The primary object of study in this research is the legal materials, namely the PBI and SEBI, which are placed in juxtaposition with the DSN-MUI Fatwa. A content analysis of the regulations was conducted, employing a conceptual approach to identify points of convergence between the PBI and the DSN-MUI fatwa. The findings reveal that the manner in which the DSN-MUI fatwa was transformed into a PBI is evident in both stylistic and substantive aspects. A variety of terms were employed to describe the contracts and the substance of the DSN-MUI fatwas, which were subsequently developed in the PBI. The pattern of transformation of the Fatwa DSN-MUI into the PBI can be identified through the analysis of three distinct patterns: the "copy and paste" pattern, the "adaptation" pattern, and the "expansion" pattern. In order to provide definitions, this approach is employed in both the general provisions and the detailed operational provisions.Artikel ini berupaya mengelaborasi Peraturan Bank Indonesia (PBI) dari tahun 2008 hingga 2023 yang berkenaan dengan perbankan syariah. PBI merupakan peraturan yang mengadopsi atau menyerap Fatwa DSN-MUI sebagai tindak lanjut ketentuan Undang-Undang tentang Perbankan Syariah yang mengamanatkan produk Fatwa DSN-MUI sebagai parameter prinsip-prinsip syariah dalam operasional perbankan syariah. Penelitian ini bertujuan untuk menjawab dua rumusan masalah yakni bagaimana bentuk perubahan Fatwa DSN-MUI ke dalam PBI tahun 2008-2023 dan pola transformasi Fatwa DSN-MUI ke dalam PBI tahun 2008-2023. Penelitian ini merupakan jenis penelitian kualitatif dengan kategori penelitian hukum normatif. Kajian utamanya berupa bahan hukum berupa PBI dan SEBI yang disandingkan dengan Fatwa DSN-MUI. Analisis yang digunakan berupa analisis konten peraturan dengan pendekatan konseptual mencari titik temu asas-asas atau prinsip yang terkait antara PBI dengan Fatwa DSN-MUI. Hasilnya menunjukkan bahwa bentuk perubahan fatwa DSN-MUI ke dalam PBI berupa penyerapan dalam ranah redaksi dan substansi. Berbagai macam nama akad dan substansi isi Fatwa DSN-MUI dipakai dan dikembangkan dalam PBI. Pola transformasi Fatwa DSN-MUI ke dalam PBI bisa diidenifikasi dalam tiga pola; pola copy paste, pola penyesuaian dan pola perluasan. Pola itu dipakai untuk memberikan definisi dalam ketentuan umum dan ketentuan detail operasionalnya.